GPS‑based slip models of one Mw 7.2 and twenty moderate earthquakes along the Sumatran plate boundary - Wong, Nathanael Z. (2020)
Earthquake-induced deformation along the Sumatran plate boundary has been monitored by the Sumatran GPS Array (SuGAr) since 2002. This continuous GPS network recorded the coseismic deformation of 10 earthquakes with moment magnitude (Mw) larger than 7 and 20 with Mw in the range of 5.9–7 from 2002 to 2013. Among all these recorded events, one large Mw 7.2 event and most of the moderate ones (5.9 ≤ Mw < 7) have yet to be modeled with available GPS data. This is partially due to the limited number (≤ 4) of stations that recorded each event. In this paper, we explore the possibility of using the limited observations to derive sensible slip models for these “forgotten” Sumatran events. We model each event as a single rectangular patch of uniform slip and constrain most of the patch parameters using external information based on slab geometry and global teleseismic catalogs. For each event, we use a grid-search approach to find the preferred location of slip patches, which we present along with contours of error-weighted variance explained to indicate the uncertainties. We compare the center locations of our final slip patches with the centroid locations from the global Centroid Moment Tensor (gCMT) catalog and the epicenter locations from four other global catalogs. Our results show that the gCMT centroid locations for the 21 Sumatran earthquakes are systematically biased toward the southwest relative to the centers of our slip patches, while the epicenter locations from the four other catalogs are all consistently shifted toward the northeast. Although the available data have no resolving power for other source parameters, we find that simple forward modeling based on sparse but reliable near-field GPS data generally provides less biased and more accurate locations than global teleseismic catalogs along the Sumatran plate boundary. The catalog of slip models we present will have particular utility in the event of other significant earthquakes being generated by the same or proximal areas of the Sunda megathrust.